UJI SENSORIS DAN PH TAPAI SINGKONG (Manihot esculenta L) DENGAN FERMENTASI AERASI - destaria erika (Jurnal BETAHPA, 2022)
Tapai is one of the original fermented foods found in Indonesia. The manufacturing process in cassava tapai contains microorganisms from tapai yeast which under anaerobic conditions will produce amylase enzymes and amyloglucosidase enzymes, two enzymes that play a role in the decomposition of carbohydrates into maltose and glucose. S. cerevisiae is a fermentative species in the fermentation process, which breaks down glucose into CO2 and strong alcohol. But in the presence of oxygen, S. cerevisiae can also carry out respiration, namely oxidizing sugar to CO2 and water. This study aims to determine the effect sensory on cassava tapai and pH. This study used a factorial randomized block design (RAKF) with two factors, namely aeration (A) (without aeration and with aeration) and fermentation time (B) (0, 24, 48, 7, and 96 hours). Parameters observed were sensory test with hedonic tests and pH. The cassava tapai preferred by the panelists in terms of aroma was the treatment with aeration, 48 hours of fermentation with an average score of 3.04, in terms of texture in the treatment without aeration, 72 hours of fermentation with an average score of 2.84, and in terms of color in the treatment without aeration, 48 hours fermentation with an average score of 3. The difference in the length of fermentation time can have a significant effect on the texture of the fermented product. the longer the fermentation it will produce softer and watery texture due to the anaerobic fermentation process that produces water (H2O). And the interaction of aeration treatment and fermentation time has a significant effect on pH.